Effects of massage on behavior of full-term newborns - Tri Sunarti Wahyutami; Soedjatmiko Soedjatmiko; Agus Firmansyah; Rulina Suradi (Indonesian Pediatric Society, 2010)
Background Baby massage is one of the touch stimulation that could be applied as soon as possible after birth. Giving massage regularly will affect the behavior of newborn.Objectives To explore the effects of ten-day massage on infant's behavior.Methods A randomized control trial was done from December 200S to March 2009. Full-term newborm were randomly assigned into massage group or control group. Babies in massage group were given massage by their mothers and supervised by midwives. All babies were evaluated twice, i.e., on day 1 and day 11, using Brazelton Scale (Neonatal Behavior Assessment Scale). The behavior was compared between the two groups.Results A total of 72 full-term newborn infants appropriate for gestational age were included in this study. Infants in the massage group sbowed significant difference in adaptive behavior compared to control group. Those adaptive behavior consisted of habituation (WMD 1.08 CI 95% 0.67 to 1.49, P<0.0001), social interaction (WMD 1.54 Cl 95% 1.23 to 1.84, P<0.0001), motor system (WMD 1.35 CI 95% 1.14 to 1.55, P<0.0001), organization state (P<0.0001), range of state (WMD 1.35 CI 95% 0.95 to 1.55, P< 0.0001), autonomic system (WMD 0.53 CI 95% 0.23 to 0.84, P<0.0001), end reflexes (P<0.0001).Conclusions Massage gives better adaptive behavior and reflexes of full-term newborns compared to those without massage.